5u – u + 3u = 14
u =
Lost your password? Please enter your email address. You will receive a link and will create a new password via email.
Please briefly explain why you feel this question should be reported.
Please briefly explain why you feel this answer should be reported.
Please briefly explain why you feel this user should be reported.
To solve the equation (5u – u + 3u = 14), follow these steps:
1. Combine the like terms on the left side:
[
(5u – u + 3u) = (5u + 3u – u) = 7u
]
2. The equation now looks like this:
[
7u = 14
]
3. To isolate (u), divide both sides by 7:
[
u = frac{14}{7} = 2
]
So, (u = 2). Great job working through it! If you need more help, feel free to ask or check the extended services page.